Safety and efficacy of the percutaneous transaxillary access for transcatheter aortic valve implantation using various transcatheter heart valves in 100 consecutive patients. (1st April 2017) - Schäfer, U.; Deuschl, F.; Schofer, N.; Frerker, C.; Schmidt, T.; Kuck, K.H.; Kreidel, F.; Schirmer, J.; Mizote, I.; Reichenspurner, H.; Blankenberg, S.; Treede, H.; et al.
Abstract: Objectives: Transcatheter Aortic Valve Implantation (TAVI) can be performed via the transaxillary approach, but data about complications and procedural outcome is limited. Introduction: TAVI is an established treatment option for patients at high risk for conventional aortic valve replacement. Nowadays, the transfemoral approach is the most commonly used access for TAVI. Nevertheless, the transfemoral access is not suitable in many patients necessitating alternative approaches. Methods: We analyzed the outcome of 100 consecutive cases receiving percutaneous transaxillary TAVI at two different hospitals. Data were retrospectively analyzed by means of procedural, hemodynamic and clinical outcome. In addition, 1st versus 2nd generation devices were analyzed. Results: Mean age was 78.2 ± 2.1 years and the logEuroSCORE I was 24.6 ± 13.9%. Transaxillary TAVI was performed in 85% via the left and in 15% via the right axillary artery. Device success was achieved in 95%. In general, there was a clear learning curve with this approach. No patient experienced a major and 11% a minor access site complication. There was one procedural death (annular rupture) and one peri-procedural TIA. 23% of the patients received a new pacemaker. At discharge, effective orifice area was 1.94 ± 0.16 cm 2 and the mean aortic gradient was 6.8 ± 2.1 mm Hg. Moderate aortic regurgitation/paravalvular leakage was documented in two patients. Mortality rates at 30 days and one year were 6% and 14.8%. Last but not least, 2nd generation devices showed improved procedural outcomes. Conclusions: The percutaneous transaxillary access for TAVI is technically feasible and safe thereby yielding excellent clinical results. Condensed abstract: We investigated In 100 consecutive patients undergoing percutaneous transaxillary transcatheter aortic valve implantation thereby demonstrating that this approach is technically feasible and safe with acceptable numbers of minor vascular complications.